Recent developments in classification criteria and diagnosis guidelines for idiopathic inflammatory myopathies. Issue 6 (November 2018) - Oldroyd, Alexander; Chinoy, Hector
Abstract : Purpose of review: The aim of this review was to summarize key developments in classification and diagnosis of the idiopathic inflammatory myopathies (IIMs). Recent findings: The recently published European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) classification criteria for the IIMs provide a comprehensive, accurate and data-driven approach to identification of IIM cases appropriate for inclusion in research studies. Further, recent studies have advanced understanding of clinical manifestations of the IIMs and delineated the role of imaging, particularly magnetic resonance. Summary: The recent publication of the EULAR/ACR classification criteria will potentially greatly improve IIM research through more accurate case identification and standardization across studies. Future inclusion of newly recognized clinical associations with the MSAs may further improve the criteria's accuracy and utility. Clear and comprehensive understanding of associations between clinical manifestations, prognosis and multisystem involvement can aid diagnostic assessment; recent advances include delineation of such associations and expansion of the role of imaging.